Digitalisasi Pengelolaan Pengetahuan Transportasi untuk Mewujudkan Smart Governance di Dinas Perhubungan Kabupaten Bogor - Neneng Rachmalia Feta; Asep Rahmat Ginanjar (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2026)
Digital transformation in public administration requires local government agencies to manage knowledge systematically as part of efforts to achieve smart governance. However, knowledge management at the Transportation Agency of Bogor Regency still faces several challenges, including knowledge gaps among human resources, the lack of integrated knowledge storage, and limited cross-departmental knowledge utilization. This study aims to develop and implement a web-based Knowledge Management System (KMS) as an effort to digitalize transportation knowledge management. The research method employed is the Knowledge Management System Life Cycle (KMSLC), which consists of knowledge identification, knowledge acquisition, system design, implementation, and evaluation stages. The system was developed using the PHP programming language with the Laravel framework and MySQL as the database management system. The results show that the developed KMS supports centralized knowledge storage and knowledge sharing across departments, facilitates the transformation of tacit knowledge into explicit knowledge, and improves organizational knowledge accessibility. The implementation of this KMS has been proven to reduce knowledge gaps among human resources and enhance work effectiveness. Therefore, the application of a web-based KMS can serve as a supporting instrument for smart governance through strengthening organizational capacity, information integration, and improving knowledge-based decision-making within the Transportation Agency of Bogor Regency.